A triple-blinded randomized controlled trial to evaluate the effectiveness of hydrotherapy versus land-based exercises outcome on pain among patients with rheumatoid arthritis - Jinjwaria, Rajendra Kumar; P. John, Rashmi; Kumar, Arvind; Kumar, Sanjay (International Journal Of Community Medicine And Public Health, 2023)
Background: The goal of the study was to determine the effectiveness of hydrotherapy versus land-based exercise outcomes to reduce pain in chronic rheumatoid arthritis (RA). Methods: A triple-blinded, randomized controlled, parallel-group, multiple arm trial was conducted between 29/09/2019 to 30/09/2021. Single centre, the study was done at the department of physical medicine and rehabilitation, KGMU (India). Eligible 90 patients were adults aged from 17 to 75 years old suffering from chronic RA) and randomization through the SNSOE method. The intervention (RJHLERA) administered was hydrotherapy exercise (Weekly 30-minute for 6 weeks exercises in a hydrotherapy bathtub, and land-based exercises (Weekly 30-minute for 6 weeks of exercises on land and 11 minutes of active exercise for the control group. NRPS scale was used for pain assessment. Results: The result revealed that pain score, In the pre-test, all the subjects had almost the same average pain score for selected subjects in each group. In the post-test, the hydrotherapy exercise group showed the maximum response with an average pain score of 3.64±1.89. the land-based exercises group showed the next to maximum response with an average pain score of 5.88±1.37 while the clear control group showed the least/poor response with an average pain score of 7.63±1.41. Hall et al and conclusion of the study is hydrotherapy produced the greatest improvement. Conclusions: The study recommends hydrotherapy and land-based exercise as safe, inexpensive interventions. Amongst hydrotherapy exercises and land-based exercises, Hydrotherapy showed the maximum (much better) to reduce the pain.